Dynamics of Shrinking Religious Freedom in Post-Reformasi in Indonesia - Hurriyah Hurriyah (Jember University Press, 2020)
Much of the studies on religious freedom in Indonesia have established a striking disconnection between constitutional protections and the actual implementation of religious freedom, underlining the state’s failure as a protector of human rights. Yet, the emphasis on human rights has overlooked why the levels of governmental restrictions are substantially increased in democratized Indonesia, creating a trend of shrinking religious freedom. Using the perspective of civic space, this study analyses the dynamics of such a trend and the involvement of the state as a primary determinant. To demonstrate how and in what way the state engages in creating shrinking religious freedom, this study uses a combination of literature reviews and inspection on past measurements on the religious freedom situation in Indonesia. This study argues that rather than ideological factors, the dynamics of shrinking religious freedom is more related to the unrelenting endeavors from state-actors and agencies to control religion for the purpose of political motives and consideration due to the changing political landscape in a democratized Indonesia.